Effect of xanthan gum on the quality of low sodium salted beef and property of myofibril proteins - Zirui Zhao; Shujie Wang; Dayu Li; Yajun Zhou (Food Science and Human Wellness)
The effects of xanthan gum (0 % and 0.3 %) on the quality of low sodium (2.0 %, 2.4 %, 2.8 %, 3.2 %, 3.6 % and 4.0 %) salted beef and property of myofibril proteins (MP) extracted from salted beef were researched. Changes in the salting absorptivity, cooking loss, shear force, color and sensory analysis showed that xanthan gum had a positive effect on the quality of salted beef with low salinity (2.0 %, 2.4 % and 2.8 %). MP of salted beef treated with xanthan gum had higher solubility, lower hydrogen bond than that without it (P < 0.05). The decrease of surface hydrophobicity and intrinsic fluorescence intensity indicated that the chromophore of protein was brought into a hydrophobic environment in the presence of xanthan gum. The electrophoresis showed that xanthan gum could improve the concentration of myosin heavy chain, paramyosin and actin after tumble-salting. The data suggested that salted beef and its MP treated with xanthan gum and 2.8 % salt (XS3) had the best properties. Together, xanthan gum could be considered as a sodium salt substitute for the development of low sodium meat products.